Search for a new partnership in trade and investment between Latin America and Asia-Pacific - Kuwayama, Mikio (IDB WashingtonUS, 2001)
Focuses on the topics such as trade relations; trade and investment links; market access and integration processes and the new Asia-Pacific-Latin America partnership.